EKSPERIMENTASI MODEL PEMBELAJARAN PROBING PROMPTING DAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR MATEMATIKA DITINJAU DARI MINAT BELAJAR SISWA KELAS VII SMP NEGERI 3 BATAM - Hanggara, Yudhi; Alfionita, Vina (UNIVERSITAS RIAU KEPULAUAN, BATAM, INDONESIA, 2015)
This research aims to find out: (1) is there any difference between the learning outcomes of students who were given the treatment model of Probing Prompting with Discovery Learning. (2) is there any difference between the learning outcomes of students who have an interest to learn high, medium and low. (3) is there any difference between the learning outcomes of students who were given the treatment modelsof Probing Prompting and Discovery Learning teach level of interest in learning. (4) is there any difference between the learning outcomes of students who have an interest to learn high, medium and lowon each model of learning. The sample of research consisted of 75 students: 37 in the first experiment class, and 38 in the second experiment class.The result of research showed that : (1) the Discovery Learning model outcomes learning better than the Probing Prompting model did. (2) The students with high interest in learning had learning outcome better than those with moderate interest in learning did, the students with high interest in learning had learning outcomme better than those with low interest in learning did, and the students with moderate interest in learning had learning outcome better than those with low interest in learning did. (3) the students with high, moderate and low interest in learning on Discovery Learning model had learning outcome better than the Probing Prompting model did. (4) on the Discovery Learning and Probing Prompting model, The students with high interest in learning had learning outcome better than those with moderate and low interest in learning did, and the students with moderate interest in learning had learning outcome better than those with low interest in learning did.Keywords: ProbingPrompting, Discovery Learning, interest in learning mathematics, Mathematics learning outcome.